Decision Recommended Food Aid Recipients Citizens Noncash In the Neighborhood Using TOPSIS Method Based Mobile: Decision Recommended Food Aid Recipients Citizens Noncash In the Neighborhood Using TOPSIS Method Based Mobile - Indra Mahendra; Mohammad Iwan Wahyuddin; Endah Tri Esthi Handayani (Institute of Computer Science (IOCS), 2020)
Non-cash Providing Food Assistance (BPNT) to the community from the government is a form of effort to Strengthen household food security, especially for poor Households. Determination of the criteria for the beneficiaries of aid is Often a complex problem, for that we need a tool to be Able to Facilitate decision making recommends that the reception of food aid the which certainly adheres to Several criteria. In the calculation for the consideration of taking a decision to receive food aid, this application uses the Technique for Others Reference by Similarity to Ideal Solution (TOPSIS) method of ranking Several alternatives from Several criteria. The results of testing the application using the TOPSIS method Obtained the highest value of 1 with the name Yusran while the manual calculation with the SAW method Obtained the highest value of 100 with the same name.